1996
DOI: 10.1016/s0896-6273(00)80193-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins Promote Astroglial Lineage Commitment by Mammalian Subventricular Zone Progenitor Cells

Abstract: The epigenetic signals that regulate lineage development in the embryonic mammalian brain are poorly understood. Here we demonstrate that a specific subclass of the transforming growth factor beta superfamily, the bone morphogenetic proteins (BMPs), cause the selective, dose-dependent elaboration of the astroglial lineage from murine embryonic subventricular zone (SVZ) multipotent progenitor cells. The astroglial inductive effect is characterized by enhanced morphological complexity and expression of glial fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
517
8
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 635 publications
(557 citation statements)
references
References 83 publications
30
517
8
2
Order By: Relevance
“…It promotes astroglial lineage determination at the expense of oligodendrogliogenesis and inhibits the differentiation of oPCs [41,42] . More recent studies showed that BMP4 is increased during demyelination.…”
Section: Bone Morphogenetic Proteinmentioning
confidence: 99%
“…It promotes astroglial lineage determination at the expense of oligodendrogliogenesis and inhibits the differentiation of oPCs [41,42] . More recent studies showed that BMP4 is increased during demyelination.…”
Section: Bone Morphogenetic Proteinmentioning
confidence: 99%
“…Previous studies have reported that neural progenitor cells of the adult SVZ can be driven to astrocytic phenotype by bone morphogenetic proteins (BMPs), in particular BMP-2 and BMP-4 [130][131][132]. High concentrations of these BMPs and their receptors have been identified in the SVZ of the adult rat brain [130,132] and may dictate the glial bias of newly generated cells in the adult subependyma.…”
Section: Suppression Of Bone Morphogenetic Proteins (Bmps) Can Be Usementioning
confidence: 99%
“…14 Similarly, BMP responses lead to apoptosis of committed populations of neural stem cells isolated from progressively older fetuses, and then to neuronal and finally glial differentiation. 15,16 We recently reported the ability of BMP-4 to efficiently promote murine ES cell differentiation towards epidermal fate and skin organogenesis in vitro. 17 In the present study, we show that a high proportion of ES cells, engaged in differentiation towards neural cell types, undergo a dose-and timedependent apoptotic cell death when treated early with BMP-4.…”
Section: Introductionmentioning
confidence: 99%